اختبار الجهد ودوره في تشخيص نقص التروية القلبية - جحجاح أكرم; رضوان عبد الناصر; الأحمد خميس مصطفى (Latakia University Journal -Medical Sciences Series, 2019)
إن اختبار الجهد هو إجراء تشخيصي وإنذاري هام في تحديد مرض نقص التروية القلبية وهناك العديد من المعطيات التخطيطية والسريرية التي يمكن من خلالها تقييم اختبار الجهد عند المريض . وفي دراستنا التي تم إجراؤها في مشفى الأسد وصلنا إلى النتائج التالية : ـ أكثر الحالات الإيجابية أظهرت موجودات تخطيطية وسريرية . ـ نسبة الإيجابية عند الرجال أكثر منها عند النساء . ـ أعلى نسبة للإيجابية كانت في عمر الـ 50 سنة ثم الـ 60 سنة ثم الـ 40 ـ 30 ـ 20 ـ ازدادت نسبة الإيجابية في حالة الألم الصدري الوصفي والاحتشاء . ـ كما بينت الدراسة أنه للحصول على أفضل قيمة للحساسية والنوعية يجب اعتماد المعيارين التاليين: * تزحل st بمقدار 1.5 مم على الأقل بشكل أفقي أو متجه للأسفل . * أو حدوث ألم خناقي . حيث بلغت الحساسية 77% والنوعية 60% . ـ وقد سـجلت 92% من التبدلات الإيجابية في فترة الراحة سـواء بالتشـارك مع فترة الجهد (84%) أو لوحدها (8%) . ـ وبالمقابل فإن صعود ST للأعلى ببطء لم يعطِ نتائج ذات أهمية كبيرة . ـ تعتبر عوامل الخطر القلبية ذات علاقة خطية مع إيجابية اختبار الجهد . ـ كلما انخفض مستوى الجهد المُجرى دلّ ذلك على سوء الإنذار . Exercise stress is an important diagnostic and prognostic procedure for identifying the patient who has ischemic disease. There are many findings in E.C.G and clinical charactristics that help us to evaluate the exercise test in the patient. In our study which performed in ALassad Hospital we obtained the following results : - Most of positive cases revealed E.C.G and clinical findings. - The higher ratio of positive types corded in the age of 50 years then 60 years then 40-30-20 years. - The ratio of positivity in men was higher than in women. - The ratio of positivity increased when there was angina or infarction . Our study reveals that if we want to get the best value of sensitivity and specifity, we must depend on two criteria: 1- Horizontal or down-sloping ST-segment depression of 1.5 m.m at least. 2- Development of Anginal pain. The sensitivity was 77 %, and specifity was 60 % and 92 % of positive changes were registered during exercise and the recovery phase. But 84 % of changes were observed during exercise and 8 % recovery phase. On the other side, the gradual up- sloping ST- depression did not give significant results . The risk factors have a linear relation with positive exercise test . The decreased level of exercise indicate a bad prognosis.